The borders that disadvantage migrant women in enjoying human rights. Issue 2 (June 2018) - Peroni, Lourdes
This article launches a frame to investigate the inequalities underlying the human rights violations migrant women may experience. Drawing on intersectionality theory and on Ratna Kapur's concept of 'normative boundaries of belonging', the article puts forward the notion of 'intersecting borders of inequality'. The notion interrogates three types of borders that may construe migrant women as outsiders or lesser members in society: formal, normative and practical borders. The article demonstrates that scrutinising the ways in which these borders intersect illuminates some of the structures disadvantaging migrant women and invites imagining wider responses to tackle these disadvantages. To illustrate these arguments, the article uses examples of the European Court of Human Rights' case law.